The Heterogenous Impact of Capital Structure Determinants: Evidence from an Emerging Economy - Akhilesh Kumar Kamalakant Yadav; Ajaya Kumar Panda; Ciorstan J. Smark; Apoorva Arunachal Hegde (Australasian Accounting, Business and Finance Journal, 2024)
Purpose: This study aims to capture the impact of firm-specific and macroeconomic variables on the capital structure of Indian companies from 2009-2021. Design/Methodology/approach: We employ the Generalized Method of Moments (GMM) as the main estimation technique and establish robustness through a panel Tobit model. Findings: The sectoral level analysis provides evidence for the heterogeneous impact of the determinant variables on the firms' leverage ratios. The results reveal that the firm-specific variables, specifically asset tangibility, effective tax rate, non-debt tax shield, net worth to total asset, firm size, net working capital ratio, liquidity, and macroeconomic variables, including foreign investment, economic growth, government borrowing, and interest rate exhibit a significant influence over capital structure. Research limitations/implications: Our study provides vital implications for manufacturing companies' finance managers to evaluate the factors affecting their capital structure. From the findings, we recommend that managers of different sectors prioritize firm-specific factors while making decisions for capital structure. Additionally, policymakers could utilize our results to determine the behaviour of macroeconomic determinants in policy formulation and amendments. Originality/Value: The sector-level analysis and the utilization of both firm-specific and macroeconomic variables in our model yields unique findings and recommendations to managers and policymakers.
Keywords: Capital Structure; Tobit Model; Pecking-order theory; GMM; Trade-off theory